A robust and quantitative assay platform for multiplexed, high throughput screening of protein kinase inhibitors. Issue 81 (21st September 2016) - Lee, Jieon; Park, Il-Soo; Park, Ginam; Cho, Kyukwang; Park, Hee-Sung; Min, Dal-Hee
Abstract : We present a new platform for multiplexed protein kinase activity assay using TiO2 decorated graphene oxide (GO), which is applicable to high throughput inhibitor screening. Abstract : We present a new platform for multiplexed protein kinase activity assay using TiO2 decorated graphene oxide (GO), which is applicable to high throughput inhibitor screening. On the basis of the strong affinity of TiO2 for the phosphate group and the fluorescence quenching capability of GO, phosphorylation of substrates by protein kinases was quantitatively measured in a short time.